Creativity, divergent thinking, attitudes, values, ideational behaviour and personality in a sample of Italian university student. - Tomassoni, Rosella; Treglia, Eugenia; Quaglieri Pantanella, Romina; Lungu, Monica Alina (Advances in Social Sciences Research Journal, 2021)
In order to understand how creativity can be developed, it is necessary a multi-dimensional approach that take into consideration the different factors that influence the creative behavior. Aim of this work is to analyze some psychological and personal variables in association with creative performance. The sample involved is composed of 1069 students attending the University of Cassino and Southern Lazio. The research has predicted the online administration of 4 types of self-report questionnaires that are part of the Runco Creativity Assessment Battery (rCAB): Divergent Thinking, DT 3Figures, Ideational Balance of Behavior, Attitudes and Values, How you would describe yourself. The data collected was inserted into the matrix and statistically analyzed through the SPSS program.